Recent Advances in Flexible Multifunctional Sensors - Ya Chang; Xiangyu Qi; Linglu Wang; Chuanbo Li; Yang Wang (Micromachines, 2023)
Wearable electronics have received extensive attention in human–machine interactions, robotics, and health monitoring. The use of multifunctional sensors that are capable of measuring a variety of mechanical or environmental stimuli can provide new functionalities for wearable electronics. Advancements in material science and system integration technologies have contributed to the development of high-performance flexible multifunctional sensors. This review presents the main approaches, based on functional materials and device structures, to improve sensing parameters, including linearity, detection range, and sensitivity to various stimuli. The details of electrical, biocompatible, and mechanical properties of self-powered sensors and wearable wireless systems are systematically elaborated. Finally, the current challenges and future developmental directions are discussed to offer a guide to fabricate advanced multifunctional sensors.